2013
DOI: 10.3389/fimmu.2013.00455
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Receptor Expression Depends More Dominantly on Differentiation and Activation than “Exhaustion” of Human CD8 T Cells

Abstract: Under conditions of chronic antigen stimulation, such as persistent viral infection and cancer, CD8 T cells may diminish effector function, which has been termed “exhaustion.” Expression of inhibitory Receptors (iRs) is often regarded as a hallmark of “exhaustion.” Here we studied the expression of eight different iRs by CD8 T cells of healthy humans, including CTLA-4, PD1, TIM3, LAG3, 2B4, BTLA, CD160, and KLRG1. We show that many iRs are expressed upon activation, and with progressive differentiation to effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
229
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(262 citation statements)
references
References 52 publications
30
229
2
1
Order By: Relevance
“…4C). LAG3 expression is upregulated on T cells after activation and differentiation, 54 , 55 and intra-tumoral T cells that recognize tumor antigens are characterized by expression of LAG3 and other inhibitory receptors. 56 Although chronic tumor antigen stimulation in the tumor microenvironment can induce T cell exhaustion with simultaneous induction of high expression of multiple inhibitory receptors, this does not mean that all CD8 + TIL which express one or more inhibitory receptors at any level are functionally exhausted.…”
Section: Discussionmentioning
confidence: 99%
“…4C). LAG3 expression is upregulated on T cells after activation and differentiation, 54 , 55 and intra-tumoral T cells that recognize tumor antigens are characterized by expression of LAG3 and other inhibitory receptors. 56 Although chronic tumor antigen stimulation in the tumor microenvironment can induce T cell exhaustion with simultaneous induction of high expression of multiple inhibitory receptors, this does not mean that all CD8 + TIL which express one or more inhibitory receptors at any level are functionally exhausted.…”
Section: Discussionmentioning
confidence: 99%
“…S3). It is important to note that in this context PD‐1 acts as an indicator of T cell activation instead of exhaustion [41]. Therefore, T RM cells from the circulation may have a promising feature of activation following TCR engagement and possibly CD103/E‐cadherin ligation once they lodge in the tumour tissue [6, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the expression of inhibitory receptors, such as PD-1 and BTLA, on human CD8 C T cells correlated with the differentiation status and was not associated with their 'exhaustion' . 37 Furthermore, T cells isolated from tumor lesions expressing either PD-1 or BTLA identified clonally expanded tumor reactive T lymphocytes that, following T cell adoptive administrations into MM patients, mediated tumor regression. 38,39 Albeit future studies need to be performed to characterize ex vivo the functional role of the T cell subsets we have found to be associated with the clinical outcome of MM patients, they could represent candidate predictive or early on treatment biomarkers for IPI plus FTM treatment.…”
Section: Discussionmentioning
confidence: 99%